Comparison of soluble E-selectin serum levels in two chronic inflammatory skindiseases - Szepietowki, J... C. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
Background: Atopic dermatitis and psoriasis are common chronic cutaneous diseases of different pathogenetic aspects. Atopic dermatitis is considered asTh-2 and psoriasis as Th-1 type dermatosis, and this difference may lead to different expression of adhesion molecules. Objectives: This study was undertaken to evaluate soluble E-selectin serum levels in atopic dermatitis and psoriasis and to correlate its expression with the disease's severity. Material and methods: 16 patients suffering from atopic dermatitis, 20 psoriatic patients and 20 healthy individuals (control group) were included into the study. Soluble E-selectin serum levels were measured by ELISA using commercially available kits (R&D Systems). Severity of atopic dermatitis was assessed according to SCORAD and of psoriasis by PASI score. Results: The average serum level of soluble E-selectin in atopic dermatitis patients was 76.6t41.7 ng/ ml and did not significantly differ from that in psoriatic patients - 60.9ž33.2 ng/ml. Soluble E-selectin serum levels both in atopic dermatitis and psoriasis were significantly increased (p<0.0002 and p<0.0005, respectively) compared to the control group, 28.7ž9.5 ng/ml. Significant correlations (p<0.02) were found between soluble E-selectin serum levels and severity of atopic dermatitis and psoriasis. Conclusion: The enhanced endothelial activity (similar degree of activation) is a characteristic phenomenon for atopic dermatitis and psoriasis. The serum expression of soluble E-selectin could be used as a marker of disease's activity.
Keywords: Blood; Dermatitis atopični; Dermatitis, atopic; E-selectin; E-selektin; Ige; Psoriasis; Psoriaza